Peran Penyuluh Pertanian dalam Mendukung Transformasi Digital Melalui Petani Apps di Sektor Pertanian Pedesaan Air Joman - Taofan Bagus Prayuda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Digital transformation in the agricultural sector is becoming increasingly important in increasing farmer productivity and efficiency. One innovation that supports this process is the use of the Farmer Apps application, a digital platform that facilitates access to information, marketing and agricultural management. This research aims to analyze the role of agricultural extension workers in supporting digital transformation through the application of Farmer Apps in the Air Joman rural area. This research method uses a qualitative approach with in-depth interviews and field observations. The research results show that agricultural extension workers have an important role as facilitators, educators and mediators in the adoption of digital technology by farmers. However, some of the challenges faced include limited digital infrastructure and low technological literacy among farmers. The conclusion of this research is the importance of increasing the capacity of agricultural extension workers and providing infrastructure capable of accelerating the digital transformation process in the rural agricultural sector.